(untitled) (Journal of Geography and Environmental Management, 2022)
Kazakhstan has a great potential for solar energy, in which photovoltaic (PV) energy technology is rapidly developing in the country, and investors are interested in the construction of photovoltaic power plants. The construction of photovoltaic power plants on the roof can save monthly electricity costs for owners and can sell excess electricity from the photovoltaic power plant to the electricity grid to gain economic benefits. The purpose of the research is to demonstrate empirical knowledge in the field of geoinformation technologies with subsequent application in the directive of the integration of alternative energy sources into everyday activities. The scientific significance of the work is justified by the widespread transition to new trends in providing electricity to cities and adjacent agglomerations, which translates into the need for practical justification using techniques of statistical analysis of spatial data based on GIS. The research methodology consists in the primary integration of Lidar technology for obtaining and processing remote sensing information using active optical systems, which in turn adds data on the phenomena of light reflection from the Earth’s surface with the designation of X, Y and Z coordinates. The main result of this work is the identification of suitable building surfaces for the subsequent installation of solar panels to generate "clean" electricity, and the conclusion outlines a reasonable potential for unloading a thermal power plant with the possibility of integrating solar energy sources. The value of this study focuses on the need to improve the quality of life of residents of Almaty, because the transition to elements of green energy will improve the environmental component, or rather reduce the load on the station, the ash content of which is 40%.